2018
DOI: 10.1038/s41419-018-0845-x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-induced autophagy via upregulation of PIASy promotes HCV replication in human hepatoma cells

Abstract: Both alcohol and hepatitis C virus (HCV) infection could induce cellular autophagy in liver cells, which is considered to be essential for productive HCV replication. However, whether alcohol-induced autophagy is involved in the pathogenesis of HCV infection is still poorly understood. Alcohol treatment could induce autophagy in Huh7 cells (a hepatoma cell line that supports HCV JFH-1 replication), evidenced by the increase of LC3B-II levels, the conversion of LC3B-I to LC3B-II, and the formation of GFP-LC3 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Acetylation of FoxO family members attenuated their transcriptional activity and reduced autophagy-related gene expression [ 82 , 83 ]. On the contrary, ethanol-induced autophagy increased the expression of PIAS family protein PIASy, which is involved in the accumulation of SUMO1-conjugated proteins, and enhanced HCV replication in hepatoma cell lines [ 84 ]. Indeed, these findings suggest that acute alcohol exposure increases autophagic flux in the liver and may prevent AFLD progression.…”
Section: Role and Regulation Of Autophagy In Afldmentioning
confidence: 99%
“…Acetylation of FoxO family members attenuated their transcriptional activity and reduced autophagy-related gene expression [ 82 , 83 ]. On the contrary, ethanol-induced autophagy increased the expression of PIAS family protein PIASy, which is involved in the accumulation of SUMO1-conjugated proteins, and enhanced HCV replication in hepatoma cell lines [ 84 ]. Indeed, these findings suggest that acute alcohol exposure increases autophagic flux in the liver and may prevent AFLD progression.…”
Section: Role and Regulation Of Autophagy In Afldmentioning
confidence: 99%
“…On the other hand, Wang and colleagues showed that the STX17-mediated homotypic fusion of phagophores enhances HCV-induced autophagosome formation to benefit HCV viral RNA replication (Table 1) [441]. Very recently, alcohol was shown to enhance PIAS family protein (PIASy) expression to activate autophagy and thus promote HCV replication (Table 1) [426]. Recent studies implied that alternatively spliced forms of ATG10 can differentially modulate autophagic flux to regulate HCV replication (Table 1) [427,428].…”
Section: Flavivirus-autophagy Interactionsmentioning
confidence: 99%
“…Similarly, fetal cortices exposed to alcohol display an increased sumoylation of the Heat shock protein 1 (HSP1), a fundamental cellular sensor of environmental proteotoxic stress, resulting in prolonged activation of HSP1 ( El Fatimy et al, 2014 ). The E3 SUMO ligase PIASy is upregulated in alcohol-treated cultured cells and drives the induction of autophagy ( Ran et al, 2018 ), a well-known mechanism involved in synapse assembly and maturation ( Tomoda et al, 2020 ). Yet, whether alcohol-dependent PIASy upregulation could contribute to synaptic dysfunction in FASD is not known.…”
Section: Discussionmentioning
confidence: 99%